Integrasi Pembelajaran Mendalam Dengan Materi Membaca Cerita Di Kelas Rendah SD - Ray Santi Pratiwi (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to analyze the integration of deep learning into story reading activities in elementary schools as an effort to improve students' literacy skills and character development. The study used a qualitative approach with a library research approach that examined various theories and relevant research findings from 2020–2025. Data were obtained from accredited national journals, scientific books, and research reports related to reading literacy, deep learning, and character education. The data analysis technique used an interactive analysis model, which included data reduction, data presentation, and conclusion drawing. The results of the study indicate that the integration of deep learning into story reading fosters integration of students' cognitive and emotional aspects. This learning encourages students to understand the text more deeply through reflection, discussion, and active involvement in the learning process. Furthermore, this approach also strengthens reflective literacy and helps students internalize the moral values ​​contained in the story. The teacher's role as a facilitator is key to creating interactive, dialogic, and meaningful learning. Furthermore, the implementation of collaborative strategies such as group discussions and creative activities has been shown to improve students' reading comprehension and social skills. Other impacts include increased reading motivation, critical thinking skills, and the development of positive character traits such as empathy, responsibility, and honesty. Therefore, integrating immersive learning into story reading is a relevant and effective approach to supporting the holistic development of literacy and character in elementary school students, in line with the demands of 21st-century education.